Crystal structure of (E)-2-(tert-butylamino)-4-(tert-butylimino)naphthalen-1(4H)-one - Lamoureux, Guy (Acta Crystallogr E Crystallogr Commun, 2018)
The title compound, C(18)H(24)N(2)O, is the first example of a naphthoquinone imine derivative isolated in the 4-imine/2-amine tautomeric form having bulky alkyl substituents at the N atoms. The molecular conformation is stabilized by an intramolecular hydrogen bond between the amine and a carbonyl group and by London attraction between the two tert-butyl groups. Only van der Waals interactions were identified in the crystal packing.